Design and development of advanced spatio temporal database models - Garima Jolly; Sunita Bhatti (Big Data and Computing Visions)
The researchers have presented a spatial database model for geometric path planning suitable for facilitating disaster management activities. The spatial queries executed using the proposed approach can reduce the computational time needed to find an optimal collision free path for network analysis. The framework is applicable to 2-dimensional and 3-dimensional workspaces. The strategy used decouples the motion planning problem into small tractable problems, which are solved using know path planning algorithm.